The effect of rural-to-urban migration on obesity and diabetes in India: a cross-sectional study. - Shah Ebrahim; Sanjay Kinra; Liza Bowen; Elizabeth Andersen; Yoav Ben-Shlomo; Tanica Lyngdoh; Lakshmy Ramakrishnan; R C Ahuja; Prashant Joshi; S Mohan Das; Murali Mohan; George Davey Smith; et al. (PLoS Medicine)
Background Migration from rural areas of India contributes to urbanisation and may increase the risk of obesity and diabetes. We tested the hypotheses that rural-to-urban migrants have a higher prevalence of obesity and diabetes than rural nonmigrants, that migrants would have an intermediate prevalence of obesity and diabetes compared with life-long urban and rural dwellers, and that longer time since migration would be associated with a higher prevalence of obesity and of diabetes. Methods and findings The place of origin of people working in factories in north, central, and south India was identified. Migrants of rural origin, their rural dwelling sibs, and those of urban origin together with their urban dwelling sibs were assessed by interview, examination, and fasting blood samples. Obesity, diabetes, and other cardiovascular risk factors were compared. A total of 6,510 participants (42% women) were recruited. Among urban, migrant, and rural men the age- and factory-adjusted percentages classified as obese (body mass index [BMI] >25 kg/m(2)) were 41.9% (95% confidence interval [CI] 39.1-44.7), 37.8% (95% CI 35.0-40.6), and 19.0% (95% CI 17.0-21.0), respectively, and as diabetic were 13.5% (95% CI 11.6-15.4), 14.3% (95% CI 12.2-16.4), and 6.2% (95% CI 5.0-7.4), respectively. Findings for women showed similar patterns. Rural men had lower blood pressure, lipids, and fasting blood glucose than urban and migrant men, whereas no differences were seen in women. Among migrant men, but not women, there was weak evidence for a lower prevalence of both diabetes and obesity among more recent (</=10 y) migrants. Conclusions Migration into urban areas is associated with increases in obesity, which drive other risk factor changes. Migrants have adopted modes of life that put them at similar risk to the urban population. Gender differences in some risk factors by place of origin are unexpected and require further exploration. Please see later in the article for the Editors' Summary.